Contrasting Reproductive Strategies of Two Nymphaea Species Affect Existing Natural Genetic Diversity as Assessed by Microsatellite Markers: Implications for Conservation and Wetlands Restoration - Parveen, Seema; Singh, Nutan; Adit, Arjun; Kumaria, Suman; Tandon, Rajesh; Agarwal, Manu; Jagannath, Arun; Goel, Shailendra (Frontiers in Plant Science, 2022)
Nymphaea, commonly known as water lily, is the largest and most widely distributed genus in the order Nymphaeales. The importance of Nymphaea in wetland ecosystems and their increased vulnerability make them a choice for conservation and management. In this work, we studied genetic diversity in a collection of 90 N. micrantha and 92 N. nouchali individuals from six different states of India i.e., Assam, Manipur, Meghalaya, Maharashtra, Goa and Kerala using simple sequence repeat (SSR) markers developed by low throughput Ilumina sequencing (10X coverage of genome) of N. micrantha. The study revealed extensive polymorphism in N. nouchali while in N. micrantha, no apparent genetic divergence was detected prompting us to investigate the reason(s) by studying reproductive biology of the two species. The study revealed that N. micrantha reproduces predominantly asexually which have impacted the genetic diversity of the species to a great extent. This observation is of immense importance for a successful re-establishment of Nymphaea species during restoration programs of wetlands. The information generated on reproductive behaviors and its association with genotypic richness can help in strategizing genetic resource conservation, especially for species with limited distribution. The study has also generated 22268 non-redundant microsatellite loci, out of which 143 microsatellites were tested for polymorphism and polymorphic markers were tested for transferability in five other Nymphaea species, providing genomic resources for further studies on this important genus.